Dynamic Modeling and Metabolic Flux Analysis for Optimized Production of Rhamnolipids. Issue 3 (3rd March 2016) - Satya Eswari, J.; Venkateswarlu, Ch.
Abstract : A comprehensive metabolic network based on the fundamental pathways representing the central metabolism of rhamnolipid by Pseudomonas aeruginosa is proposed and a dynamic model compatible with the underlying metabolic network is developed involving the macro-reactions derived from the elementary flux modes of the reaction network. The experimentally validated mathematical model is then coupled with a global optimization technique called differential evolution (DE) to optimize the medium composition as well as the extracellular and intracellular fluxes of the metabolic network. The analysis of the results shows the usefulness of the integrated approach involving the development of a dynamic model based on the metabolic network structure and model-based optimization of the medium composition and metabolic fluxes by an efficient evolutionary optimization technique to enhance the productivity of rhamnolipid.